Rapid Nanopore Assay for Carbapenem-Resistant Klebsiella pneumoniae - Niu, Haofu; Zhang, Weili; Wei, Liangwan; Liu, Meng; Liu, Hao; Zhao, Changjian; Zhang, Peng; Liao, Quanfeng; Liu, Ya; Yuan, Qingyue; Wu, Siying; Kang, Mei; et al. (Frontiers in Microbiology, 2019)
The prevalence of carbapenem-resistant Klebsiella pneumoniae (CRKP) is rapidly increasing worldwide in recent decades and poses a challenge for today's clinical practice. Rapid detection of CRKP can avoid inappropriate antimicrobial therapy and save lives. Traditional detection methods for CRKP are extremely time-consuming; PCR and other sequencing methods are too expensive and technologically demanding, making it hard to meet the clinical demands. Nanopore assay has been used for screening biomarkers of diseases recently because of its high sensitivity, real-time detection and low cost. In this study, we distinguished CRKP from carbapenem-sensitive K. pneumoniae (CSKP) by the detection of increasing amount of extracted 16S ribosomal RNA (16S rRNA) from bacterial culture with antibiotics imipenem, indicating the uninhibited growth of CRKP by the imipenem. Specific signals from single channel recording of 16S rRNA bound with probes by MspA nanopore allowed the ultra-sensitive and fast quantitative detection of 16S rRNA. We proved that only 4 hours of CRKP culture time was needed for nanopore assay to distinguish the CRKP and CSKP. The time-cost of the assay is only about 5% of disk diffusion method while reaching the similar accuracy. This new method has the potential application in the fast screening of drug resistance in clinical microorganism samples.